Effect of lymphotoxin blockage on different stages of Sjogren's syndrome in an animal model. Issue 2 (29th June 2022) - Jacob, Alexander; Shen, Long; He, Jing; Nealon, Kelly; Alexander, Jessy J.; Ambrus, Julian L.
Abstract: Background: Lymphotoxin (LT) is an important mediator in Sjogren's syndrome (SS), both in patients and in animal models. Deletion of the LT alpha gene prevented the development of disease manifestations in the interelukin alpha transgenic mouse (IL14αTG) mouse model of SS. Aims: The current study was designed to evaluate the use of LT inhibitors at different stages of the disease in IL14αTG mice. Materials and Methods: IL14αTG mice were treated with anti‐LTa monoclonal antibody, LTb receptor‐immunoglobulin fusion protein (LTBR‐Ig) or isotype control during different stages of disease and analysis of salivary gland function, immunoglobulins, autoantibodies and histology of internal organs performed. Results and Discussion: The inhibitors were very effective in maintaining salivary gland function and preventing infiltration of the glands with lymphocytes when used in the early stages of the disease. Blocking LT at later stages of the disease did not recover salivary gland function but was still effective in limiting extra glandular manifestations including eye disease and tumor development. Some differences were noted in the effectiveness of anti‐LTα versus LTBR‐Ig in limiting particular disease manifestations. Conclusion: LT inhibitors deserve further investigation in the management of SS at whatever stage is identified. Key point: Blocking lymphotoxin in an animal model of Sjogren's syndrome in shown to block disease progression when used at both early and later disease stages.